A novel PIGA mutation in a Taiwanese family with early-onset epileptic encephalopathy. (May 2018) - Lin, Wei-De; Chou, I-Ching; Tsai, Fuu-Jen; Hong, Syuan-Yu
Abstract: Purpose: We report the first family with PIGA- associated epileptic encephalopathy in Taiwan and hope to elucidate its special phenotype and inheritance pattern. Method: We found a Taiwanese family with several members suffered from severe epileptic encephalopathy (ZY07, ZY01, ZY04). To determine the underlying etiology, whole exome sequencing was conducted. Results: A single novel variant, NM_002641: c.356G > A, p.Arg119Gln, was identified in the X chromosome PIGA gene in our proband patient (ZY07). The patient's mother (ZY02) and aunt (ZY03) were confirmed as carriers of the hemizygous variant. Conclusions: This paper highlights the highly transmitted features of PIGA and other X-linked EIEEs, raising awareness of rare forms of epileptic encephalopathy.